2021
DOI: 10.1080/1461670x.2021.1990788
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Out the News. A Cross-Media Perspective on News Avoidance Practices of Young News Users in Flanders During the COVID-19 Pandemic

Abstract: The coronavirus pandemic sent tremors throughout the news landscape. While the onset of the pandemic appeared to significantly increase news hunger, soon after, studies reported an uptick in what they termed "coronablocking": the conscious avoidance of coronavirus related news. Younger age groups in particular appeared more likely to engage in coronablocking. This article seeks to contribute to extant research by providing a textured account of how and why young news users avoid the news. To explore these ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Finally, regarding news avoidance, it is not possible to determine whether those accessing news from any of these sources are actively avoiding the news elsewhere. Nor is it possible to determine if the updates from these official sources and experts are permeating through some sort of news avoidance barrier -the particular 'coronablocking' which Vandenplas et al (2021) described -or whether those receiving these updates are those still actively and willingly consuming news content. Given the various waves of Covid-19 (Delta and Omicron appeared in late 2021), high case numbers and continued deaths in late 2021 and early 2022, it would be surprising if both information overload and the negative nature of news -both identified by Skovsgaard & Andersen (2020) as factors affecting those who were seeking to avoid exposure to news updates -were not relevant when considering any dips in news consumption habits.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, regarding news avoidance, it is not possible to determine whether those accessing news from any of these sources are actively avoiding the news elsewhere. Nor is it possible to determine if the updates from these official sources and experts are permeating through some sort of news avoidance barrier -the particular 'coronablocking' which Vandenplas et al (2021) described -or whether those receiving these updates are those still actively and willingly consuming news content. Given the various waves of Covid-19 (Delta and Omicron appeared in late 2021), high case numbers and continued deaths in late 2021 and early 2022, it would be surprising if both information overload and the negative nature of news -both identified by Skovsgaard & Andersen (2020) as factors affecting those who were seeking to avoid exposure to news updates -were not relevant when considering any dips in news consumption habits.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…They identify three reasons why people avoid the news: scepticism and issues around trust of news outlets; a sense of information overload; and the negativity bias of news, which can be associated with a sense of helplessness and impact on mood. Vandenplas et al (2021) draw on the term 'coronablocking' among those avoiding pandemic-related news content, while another study highlighted the seemingly contradictory but undeniable trend of Covid-19 leading to an increase in news consumption and also an increase in news avoidance (de Bruin et al, 2021). This leads, the authors of the latter study argue, to a 'dilemma' for citizens in 'striking a balance between consuming enough news to be well-informed while simultaneously not consuming too much to avoid detrimental effects on mental well-being' (de Bruin et al, 2021(de Bruin et al, , p. 1299.…”
Section: Consuming and Avoiding Covid Newsmentioning
confidence: 99%
“…News use through the pandemic is a topic that has attracted considerable scholarly interest (Broersma and Swart, 2021; Mihelj et al, 2021; Newman, 2021; Van Aelst et al, 2021). Studies in different countries have found similar patterns of intensified news use in early 2020, but also documented experiences of information overload and news fatigue as the pandemic continued (Ytre-Arne and Moe, 2021; Nguyen, n.d.; De Bruin et al, 2021; Groot Kormelink and Klein Gunnewiek, 2021; Vandenplas et al, 2021; Mannell and Meese, 2022). The studies indicate partly different findings on the meaning of metrics in pandemic news: Groot Kormelink and Klein Gunnewiek (2021) quote young news uses who declared daily numbers were not important, but also find that modes of information-seeking and avoidance seemed to fluctuate with infection rates.…”
Section: Valuable Journalism In Pandemic Crisismentioning
confidence: 99%
“…Our findings correspond here with several studies on how news users balanced information needs and attempts to avoid overload, in an emotionally charged situation (eg. De Bruin et al, 2021; Vandenplas et al, 2021). Monitoring the infection rate was an important part of the new, intensified news media repertoire:Oh yes, absolutely, so, from March 12th and to the end of May I guess [...] I used the media much more to an extreme degree.…”
Section: Analysis: Monitoring the Infection Ratementioning
confidence: 99%
“…In-depth interviews with Belgian news users (21–33 years old) who experienced changed news habits since the beginning of the pandemic provide insights into the contradictory explanations of increased news consumption and news avoidance ( Vandenplas et al, 2021 ). Initially, people wanted to be up to date about the measures and numbers, wanted to share their insecurities, talked about the news with others, and believed that the news about COVID-19 was inescapable.…”
Section: A Model Of News Avoidancementioning
confidence: 99%